The Influence of Carbon Emission and Monetary Instruments on Economic Growth in Indonesia (In Press) - Atika Fatimah; Ismadiyanti Purwaning Astuti Astuti (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2026)
Over the past three decades, Indonesia’s economic growth has been quite fluctuating, as evidenced by the occurrence of quite severe contraction due to the impact of two major crises which caused a deep recession. This study aims to look at the influence of carbon emissions consisting of independent variables of carbon emissions from waste, carbon emissions from transportation pollution, electricity production from renewable energy and the influence of monetary policy instruments consisting of two independent variables, namely loan interest rates and portfolio investments, on dependent variables, namely economic growth proxied by Gross National Income (GNI growth) data. This study uses secondary data obtained from the World Bank and the Central Statistics Agency (BPS). This secondary data is in the form of a time series of 30 years, from 1994 to 2023. The analysis method of this study uses the Error Correction (ECM) Model. The results of the long-term study found that carbon emissions from waste and loan interest rates had a negative and significant influence on economic growth, while carbon emissions from transportation pollution, electrical products from renewable energy and portfolio investments had no effect on economic growth. If the government has a goal to increase economic growth, carbon emissions from waste and loan interest rates must be lowered. Reduced carbon emissions from waste will reduce pollution which will have an impact on increasing production, quality of health and human resources which will increasing productivity which will ultimately have an impact on increasing economic growth. In the short term, the results of the study stated that carbon emissions from transportation pollution and portfolio investments have a positive and significant effect on economic growth, while loan interest rates have a negative and significant effect on economic growth. On the other hand, carbon emissions from waste and electrical products from renewable energy have no effect on economic growth. Increasing carbon emissions from transportation pollution mean that people in developing countries such as Indonesia use vehicles for productive activities so that it will increase economic growth. Increased portfolio investment will increase capital in a company so that it will increase profits which will have an impact on increasing economic growth. Loan interest rates that decline in the short term will encourage people to make loans for consumption or production so that it will increase economic growth. Keywords: carbon emission, monetary instruments, economic growth, error correction model JEL: E52, O44, Q43